In vivo study of rat cortical hemodynamics using a stereotaxic‐apparatus‐compatible photoacoustic microscope. Issue 9 (11th May 2018) - Guo, Heng; Chen, Qian; Qi, Weizhi; Chen, Xingxing; Xi, Lei
Abstract : Brain imaging is an important technique in cognitive neuroscience. In this article, we designed a stereotaxic‐apparatus‐compatible photoacoustic microscope for the studies of rat cortical hemodynamics. Compared with existing optical resolution photoacoustic microscopy (ORPAM) systems, the probe owns feature of fast, light and miniature. In this microscope, we integrated a miniaturized ultrasound transducer with a center frequency of 10 MHz to detect photoacoustic signals and a 2‐dimensional (2D) microelectromechanical system (MEMS) scanner to achieve raster scanning of the optical focus. Based on phantom evaluation, this imaging probe has a high lateral resolution of 3.8 μm and an effective imaging domain of 2 × 2 mm 2 . Different from conventional ORPAMs, combining with standard stereotaxic apparatus enables broad studies of rodent brains without any motion artifact. To show its capability, we successfully captured red blood cell flow in the capillary, monitored the vascular changes during bleeding and blood infusion and visualized cortical hemodynamics induced by middle cerebral artery occlusion. Abstract : Brain imaging is an important technique in cognitive neuroscience. We propose a stereotaxic‐apparatus‐compatible photoacoustic microscope, which can be used to observe the rat cortical hemodynamics in vivo. Combined with stereotaxic apparatus, this new microscope is able to get clear and stable vasculature in any regions over the entire rat cortical area.